Estimating the undegradable intake protein content of two forages by different commercial proteases - I.E.O. Abdelgadir; R.C. Cochran; E.S. Vanzant; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1997)
We evaluated the potential of several commercially available proteases for use in predicting the undegradable intake protein (UIP) concentrations o f alfalfa and prairie hay. Protease s differed in their estimates o f the rate of forage protein breakdown an d the amounts of different forage protein fractions . At least one protease appeared to yield acceptable predictions of UIP via a short-term, single time-point assay. Assays of this type deserve further consideration for commercial application.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Protein degradability; Proteases; Forages